Age-Related Variation On Somatotypes Of Javanese People In Y Ogyakarta Province - Kumi Ashizawa, Nani Trilusiana Rahmawati Janatin Astuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Body form has been related to a variety of behavioral, occupational, health, and physical performance variables, and somatotype is an effective technique for the study of anthropometric variations, which possess constantly recognizable characteristics and are the functional end products of the whole genetic and the developmental complex.Objective: The objective of this cross-sectional study was to describe age-related variations of somatotype in a cross sectional sample of healthy adult and elderly subjects from Yogyakarta Province Indonesia, and to promote the use of technique for the study of somatotype variations in aged populations.Methods: The study groups, consisted of 426 healthy Javanese people (185 males and 241 females) of age 18 - 90 years. The men and women samples were further divided into four groups: 18 - 20 years, 21 - 40 years, 41 - 60 years, and 61 - 90 years. All subjects were born and resident in Yogyakarta Province. Heath-Carter somatotypes were determined for all subjects.Result: The height and weight are significantly greater in males than in females. There was the relationship between age and somatotype component. The mean somatotype of the overall Javanese sample (18-90 years) is 3.0 - 3.2 - 2.9 or center type (SO: 1.2 - 1.3 - 1.3) in males and 4.4 - 3.3 - 2.2 or mesoendomorphic type (SO: 1.2 - 1.5 - 1.3) in females.Conclusion: In general, endomorphy and ectomorphy showed a week and even negative correlation with age group, while mesomorphy show a low but positive correlation. Significant sex differences in somatotype appeared only in endomorphy where females were higher than males. Javanese males somatotypes were less endomorphic and ectomorphic, but more ectomorphic than Javanese females.Key words: somatotype component - body size - variation - Javanese people